Mutual funds system in Ukraine - Bundzylo, Mariya (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
In people’s search for the best way to enrich and protect wealth there appeared collective investment institutions. This is a good alternative for investors who are not satisfied with bank deposit’s interest rates. Сollective investment institutions СІІs are the new opportunity for Ukrainian investors to invest their savings so as to ensure their growth. The Ukrainian history of mutual funds began with the adoption of the appropriate law in 2001. Still, besides the real advantages of this kind of investing there are numerous disadvantages, especially in conditions of transition economy of Ukraine.
Keywords: instytuty wspólnego inwestowania; inwestycje; aktywa; inwestycyjne fundusze; przekształcenia rynkowe; udziałowe inwestycyjne fundusze; korporacyjne inwestycyjne fundusze; akcjonariusze; dywidendy